Aplicación Del Análisis Envolvente De Datos En Las Universidades Autónomas De Bolivia. Caso Carreras Ciencias Empresariales - Minaya, Wendy Roxana Jordán; Fernández, Gabith Miriam Quispe (European Scientific Journal, ESJ, 2017)
The technical efficiency is a tool that allows to know the situation in which an institution is located. In this context, the objective of the research is to determine the technical efficiency indices of the years 2014 and 2015 in order to carry out a comparative analysis and identify their causes in the careers related to the Economic and Business Sciences of the State Autonomous Public Universities Plurinacional de Bolivia through the application of Data Envelopment Analysis (DEA) as a tool for analysis of technical efficiency. The research constitutes the first work of analysis of university efficiency. 69 studies belonging to 11 Universities of the Bolivian University System are considered as study population. The results show that there are careers with high indices of technical efficiency; on average, there is an increase in technical efficiency between 2014 and 2015; the number of students, graduates and teachers are what determine the rates of technical efficiency in careers.